Oxidization of squalene, a human skin lipid: a new and reliable marker of environmental pollution studies. (2nd March 2015) - Pham, D.‐M.; Boussouira, B.; Moyal, D.; Nguyen, Q.L.
Synopsis A review of the oxidization of squalene, a specific human compound produced by the sebaceous gland, is proposed. Such chemical transformation induces important consequences at various levels. Squalene by‐products, mostly under peroxidized forms, lead to comedogenesis, contribute to the development of inflammatory acne and possibly modify the skin relief (wrinkling). Experimental conditions of oxidation and/or photo‐oxidation mechanisms are exposed, suggesting that they could possibly be bio‐markers of atmospheric pollution upon skin. Ozone, long UVA rays, cigarette smoke… are shown powerful oxidizing agents of squalene. Some in vitro, ex vivo and in vivo testings are proposed as examples, aiming at studying ingredients or products capable of boosting or counteracting such chemical changes that, globally, bring adverse effects to various cutaneous compartments.